DISTRIBUSI SPASIAL GASTROPODA Littoraria scabra DI HUTAN MANGROVE PULAU TUNDA SERANG BANTEN, INDONESIA - Syahrial Rial; Nanang Karsim (Department of Marine Sciences, Faculty of Marine Science and Fisheries, Udayana University, 2018)
Gastropods is the most dominant molusc group in the mangrove forest. The Spatial Distribution Study of Gastropoda Littoraria scabra in the Mangrove Forest of Serang Banten Island has been conducted in January 2014. It aims to provide information on the spread of Indonesian biodiversity especially L. scabra. Data collection of L. scabra gastropods is done by making line transects and plots drawn from the reference point (the outer mangrove stand) and perpendicular to the coastline to the mainland. The line transect is made of plots with size 10 X 10 m and in the size of 10 x 10 m, a small plot of 1 x 1 m of 5 plots is created. The results showed that L. scabra gastropod was distributed evenly in the mangrove forest of Pulau Tunda Serang Banten. Then the composition and density are higher in the East (284 individu and 6.31 ind/m2) than in the South (101 individu and 2.24 ind/m2). In addition, the results also showed that the distribution pattern of L. scabra gastropod in the mangrove forest of Tunda Serang Banten Island was uniform (I? <1), indicated that L. scabra gastropod disperse evenly in it’s mangrove forest. Keywords: distribution, gastropod, Littoraria scabra, mangrove, Tunda Island, Indonesia